100 Anti-retroviral exposure and somatic mitochondrial DNA mutations. Issue 3 (9th February 2012) - Payne, B A I; Pfeffer, G; Price, D A; Chinnery, P F
Abstract : Many nucleoside analogue antiretroviral drugs (NRTIs) impair mitochondrial DNA (mtDNA) replication leading to reversible mtDNA depletion. It is unknown whether these drugs additionally cause mtDNA mutation. We recruited 35 HIV infected persons aged 50 years and under. Subjects were stratified by lifetime NRTI exposure. Skeletal muscle biopsies were subjected to COX (cytochrome-c oxidase) histochemistry, and individual fibres were laser captured for molecular analyses. Untreated patients showed negligible COX defects (mean 0.1%, SD 0.1%). Heavily NRTI-treated patients showed high level COX defects (mean 3.0%, SD 3.4%, maximum 9.8%). Difference between groups was statistically significant (p=0.002). Molecular analysis of individual COX-deficient fibres from treated subjects showed that the majority contained high proportional levels of mtDNA large-scale deletion mutations (41/70 fibres, 59%). Deleted species comprised a variety of mutations, each clonal within an individual fibre. No deleted mtDNA was detected in adjacent normal fibres. Furthermore, full mt genome sequencing of individual COX-deficient fibres revealed acquired mtDNA point mutations in both mtDNA coding and non-coding regions. For the first time we show that acquired mtDNA mutation in post-mitotic tissue occurs in the setting of antiretroviral treatment with NRTIs known to inhibit mtDNA replication. Importantly, mtDNA damage appeared to persist despite prior cessation of these drugs. The pattern of mtDNA damage we observe appears to be an acceleration of that expected during healthy ageing, suggesting the potential for increased frailty and late-onset neurological disease in this patient group.